Influencia del clima organizacional en la mejora de la satisfacción laboral de los docentes de la institución educativa particular Benjamin Franklin School de Chepén, año 2016 - Zeña Torres, Jessica Milagros (2016)
This research is descriptive transactional, aims to determine the influence of the organizational climate on the improvement of job satisfaction of teachers of Private Educational Institution Benjamin Franklin School, 2016 ". The Private Educational Institution "Benjamin Franklin School" is a non-profit institution dedicated to teaching at the elementary, primary and secondary levels. The sample comprises the entire population, which is composed of 20 teachers. The collection instrument used is the survey, which has been applied to teachers of the Educational Institution "BENJAMIN FRANKLIN SCHOOL". This survey was designed to solve two research variables. To identify the organizational climate of the institution, the dimensions evaluated were: Structure, Responsibility, Reward, Challenge, Relations, Cooperation, Standards, Conflict, Identity. And to measure job satisfaction I had as a reference the dimensions: Physical conditions and / or materials, labor benefits and / or remunerative, administrative policies, social relationships, personal development, task performance, relationship with authority. As to the organizational climate almost all dimensions yielded favorable results, except in the responsibility dimension, as this reflects a low level of satisfaction, because teachers do not have the necessary decision-making power without requiring the approval of their boss and in the challenge dimension since teachers do not receive training they feel that the institution does not provide them opportunities to make innovative and different things in their work. With respect to the dimensions of job satisfaction the results are also favorable in most analyzed aspects, except for personal development and relationship with authority dimension, which has its origin in the limited power of autonomy in decision-making.